On the Problem - Subject of Interpretative Case № 4 of 2019 of the Supreme Administrative Court - Radev, Stefan (Research Papers, 2021)
The article discusses interpretative Case № 4/2019 of the Supreme Administrative Court (SAC). The purpose of the work is to answer the question posed in the interpretative case, with the following tasks to achieve it: analysis of the relevant legislation and interpretive practice. The methods of analysis, comparison and synthesis are applied and as a result one of the two positions of the supreme administrative judges is supported.